1931 S.C. Acts 78, No. 58, § 1 - (:unkn) unknown (General Publisher, 1931)
Prohibited the setting of any loaded trap gun or spring gun. Punishable by a fine of $100-500 or imprisonment of 30 days to 1 year.
--
Keywords: TRAP GUNS